Analysis of the Role of Internal Audit in Enhancing Company's Internal Control - Anwar, Fadhilah Rahma (Golden Ratio of Auditing Research, 2022)
The qualitative investigation into auditing strategies within multinational companies aims to explore and understand the effectiveness of various approaches in addressing fraud risks. Employing purposive sampling, key stakeholders including senior executives, auditors, and regulatory authorities were interviewed. Additionally, document analysis was conducted on relevant organizational documents. Thematic analysis was employed to derive patterns and insights from the data. Findings reveal that internal auditing plays a foundational role in assessing internal controls and identifying vulnerabilities, while external audits enhance transparency despite concerns about auditor independence. Forensic auditing emerges as crucial in uncovering fraudulent activities, and the integration of data analytics shows promise in enhancing fraud detection capabilities. Contextual factors such as geographic dispersion and cultural diversity present challenges, while stakeholder perceptions underscore the strategic importance of effective fraud risk management. Recommendations include prioritizing proactive measures, fostering collaboration, and strengthening corporate governance mechanisms to mitigate fraud risks effectively. This research contributes insights into enhancing fraud risk management practices within multinational corporations.